Design quality in building behavioral intention through affective and cognitive involvement for e-learning on smartphones. Issue 6 (7th July 2020) - Faisal, Chaudhry Muhammad Nadeem; Fernandez-Lanvin, Daniel; De Andrés, Javier; Gonzalez-Rodriguez, Martin
Abstract : Purpose: This study examines the effect of design quality (i.e. appearance, navigation, information and interactivity) on cognitive and affective involvement leading to continued intention to use the online learning application. Design/methodology/approach: We assume that design quality potentially contributes to enhance the individual's involvement and excitement. An experimental prototype is developed for collecting data used to verify and validate the proposed research model and hypotheses. A partial-least-squares approach is used to analyze the data collected from the participants ( n = 662). Findings: Communication, aesthetic and information quality revealed to be strong determinants of both cognitive and affective involvement. However, font quality and user control positively influence cognitive involvement, while navigation quality and responsiveness were observed as significant indicators of affective involvement. Lastly, cognitive and affective involvement equally contribute to determining the continued intention to use. Research limitations/implications: This study will draw the attention of designers and practitioners towards the perception of users for providing appropriate and engaging learning resources. Originality/value: Prevalent research in the online context is focused primarily on cognitive and utilization behavior. However, these works overlook the implication of design quality on cognitive and affective involvement.